Permethrin-treated baby wraps for the prevention of malaria in children: Protocol for a double-blind, randomized placebo-controlled controlled trial in western Uganda - Ross M. Boyce; Caitlin Cassidy; Ronnie Ndizeye; Emma Baguma; Dana Giandomenico; Bonnie E. Shook-Sa; Moses Ntaro; Raquel Reyes; Edgar M. Mulogo (PLoS ONE, 2023)
This article details the study protocol for a double-blind, randomized placebo-controlled trial to determine the effectiveness of permethrin-treated baby wraps to prevent Plasmodium falciparum malaria infection in children 6–24 months of age. Participating mother-infant dyads will be randomized to receive either a permethrin-treated or a sham-treated wrap, known locally as a “lesu.” After a baseline home visit, during which time all participants will receive new long-lasting insecticidal nets, participants will attend scheduled clinic visits every two weeks for a period of 24 weeks. In the event of an acute febrile illness or other symptoms that may be consistent with malaria (e.g., poor feeding, headache, malaise), participants will be instructed to present to their respective study clinic for evaluation. The primary outcome of interest is the incidence of laboratory-confirmed, symptomatic malaria in participating children. Secondary outcomes of interest include: (1) change in children’s hemoglobin levels; (2) change in children’s growth parameters; (3) prevalence of asymptomatic parasitemia in children; (4) hospitalization for malaria in children; (5) change in the mother’s hemoglobin level; and (6) clinical malaria in the mother. Analyses will be conducted using a modified intent-to-treat approach, with woman-infant dyads who attend one or more clinic visits analyzed according to the arm to which they were randomly assigned. This is the first use of an insecticide-treated baby wrap for prevention of malaria in children. The study began recruitment in June 2022 and is ongoing. ClinicalTrials.gov Identifier: NCT05391230, Registered 25 May 2022.